Wafer‐Scale Oxygen‐Doped MoS2 Monolayer. Issue 6 (10th April 2021) - Wei, Zheng; Tang, Jian; Li, Xuanyi; Chi, Zhen; Wang, Yu; Wang, Qinqin; Han, Bo; Li, Na; Huang, Biying; Li, Jiawei; Yu, Hua; Yuan, Jiahao; et al.
Abstract: Monolayer MoS2 is an emergent 2D semiconductor for next‐generation miniaturized and flexible electronics. Although the high‐quality monolayer MoS2 is already available at wafer scale, doping of it uniformly remains an unsolved problem. Such doping is of great importance in view of not only tailoring its properties but also facilitating many potential large‐scale applications. In this work, the uniform oxygen doping of 2 in wafer‐scale monolayer MoS2 (MoS2− x O x ) with tunable doping levels is realized through an in situ chemical vapor deposition process. Interestingly, ultrafast infrared spectroscopy measurements and first‐principles calculations reveal a reduction of bandgaps of monolayer MoS2− x O x with increased oxygen‐doping levels. Field‐effect transistors and logic devices are also fabricated based on these wafer‐scale MoS2− x O x monolayers, and excellent electronic performances are achieved, exhibiting promise of such doped MoS2 monolayers. Abstract : In this work, the in situ oxygen doping of wafer‐scale monolayer MoS2 through chemical vapor deposition is reported. The doped films (MoS2− x O x ) are uniform with tunable doping levels and their bandgaps decrease with the increased oxygen concentrations. Monolayer MoS2− x O x field‐effect transistors and logic devices are fabricated and show excellent electronic performances.